2007
DOI: 10.1017/s1068280500007115
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Environmental and Health Motivations on the Organic Share of Produce Purchases

Abstract: As demand and supply of organic produce has increased, it has become possible to distinguish between the many individuals that express a preference for organic and the share of their purchases that is organically produced. This study examines the share of a consumer's produce purchases that are organic, and how that is influenced by economic factors, environmental and health motivations, and demographic characteristics. Results from a model of organic preference are compared to those from a model of organic bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
41
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 25 publications
(28 reference statements)
3
41
0
3
Order By: Relevance
“…According to Aertsens et al [29], age does not seem to have an influence in shaping organic food consumption, or only slightly. Other research shows that younger people have a more positive attitude towards organic products than older people and are willing to pay a price premium although their purchasing frequency is rather low [2,30,31]. This allows us to formulate a first hypothesis: Hypothesis 1.…”
Section: Characteristics Of Demand For Organic Food Productsmentioning
confidence: 99%
“…According to Aertsens et al [29], age does not seem to have an influence in shaping organic food consumption, or only slightly. Other research shows that younger people have a more positive attitude towards organic products than older people and are willing to pay a price premium although their purchasing frequency is rather low [2,30,31]. This allows us to formulate a first hypothesis: Hypothesis 1.…”
Section: Characteristics Of Demand For Organic Food Productsmentioning
confidence: 99%
“…The research is strongly suggestive, but not conclusive, that higher-income households are more likely to purchase organic food (Dimitri & Dettmann, 2012;Govindasamy & Italia, 1990;Loureiro, McCluskey, & Mittlehammer, 2001). That said, Durham (2007) found that income is unrelated to the purchase of organic food. Following the literature on consumers of organic food, Figures 2 and 3 demonstrate how organic food availability in this dataset varies with education and income.…”
Section: Spatial Analysis Of Organic Food Availabilitymentioning
confidence: 99%
“…Future research into the relationship between access to organic food for black households is warranted; it is likely that a complicating factor is related to the general barriers to food access caused by a lack of food stores or the type of food stores in neighborhoods with mostly black residents. Recent research relating the likelihood of consuming organic food with income has yielded inconclusive results, with some finding that households with higher income are more likely to buy organic food and others suggesting that income is not statistically related to the likelihood of buying organic food (Durham, 2007;Govindasamy & Italia,1990;Loureiro et al, 2001). Because income and education are highly correlated, it is difficult to isolate the effects of education and income on behavior, including food access.…”
Section: Socioeconomic Characteristics and Organic Food Availabilitymentioning
confidence: 99%
“…The choice of demographic characteristics mapped follows from the literature on organic food consumers, which finds that, after accounting for income and other factors, consumers with higher levels of education are more willing or likely to purchase organic products (Dettmann & Dimitri, 2010;Fotopoulos & Krystallis, 2002;Krystallis, Fotopoulos, & Zotos, 2006;Magnusson, Arvola, Koivisto Hursti, & Åberg, 2001;O'Donovan & McCarthy, 2002;Zepeda & Li, 2007). Research has yielded conflicting results on the impact of income and race on the likelihood of buying organic food (Durham, 2007;Govindasamy & Italia, 1990;Loureiro, McCluskey, & Mittlehammer, 2001). Access to organic food, approximated by distance to a Whole Foods retail store, suggests that availability likely has a measurable effect on consumption of organic food (Dimitri & Dettman, 2011).…”
mentioning
confidence: 99%